EFFECT OF MARKETING MIX STRATEGY 4PS ON CONSUMER BUYING DECISION IN W FOUR UNIPESOAL SUPERMARKET LDA MUNICIPIO DILI, EAST TIMOR - Fernandes, Domingos; S. Guterres, Alexandre de; Concieção, Olinda da; Guterres, Antonio (Ridwan Institute, 2025)
Economic development in Timor-Leste requires the private sector to grow and diversify to support sustainable economic progress. Without well-implemented policies and programs that promote private sector development, the country risks losing the opportunity to manage secure and sustainable sources of wealth. This research aims to analyze the influence of the marketing mix 4Ps strategy (product, price, place, and promotion) on buyer decisions at Supermarket W Four Unipessoal Lda, Dili Municipality, Timor Leste. The benefits of this research are that it expands knowledge regarding consumer behavior influenced by marketing strategies in the retail sector in Timor-Leste. This study employed a qualitative research design, with data collected through purposive sampling of 10 respondents. The data collection process occurred from September 10, 2023, to October 31, 2023. Data were gathered using interviews and observations, and the analysis was conducted using the Miles and Huberman model, which emphasizes qualitative descriptive analysis. The findings of this study indicate that all elements of the 4Ps marketing mix significantly influence buyer decisions, with the product and price variables being the most dominant factors in the purchasing process. Promotion and place factors also play important supporting roles. The conclusion drawn from this study is that an effective marketing mix strategy can enhance buyer decisions and overall business performance. The implication of this research suggests that Supermarket W Four Unipessoal Lda needs to continuously improve the quality of its products and implement innovative marketing strategies to remain competitive in the growing retail market of Timor Leste.